2022
DOI: 10.1002/ana.26509
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Low‐Frequency Repetitive Transcranial Magnetic Stimulation after Ischemic Stroke in Rats

Abstract: Objective: Stroke is a leading cause of human death and disability. Effective early treatments with reasonable therapeutic windows remain critically important to improve the outcomes of stroke. Transcranial magnetic stimulation (TMS) is an established noninvasive technique that has been applied clinically and in animal research for multiple brain disorders, but few studies have examined acute neuroprotection against ischemic stroke. The present investigation tested the novel approach of low-frequency repetitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Evidence-based translational barriers: (a) Preclinical response domains . Most preclinical studies (approximately 60%) focused on the use of tDCS or rTMS to promote neuroprotection and plasticity after stroke in relation to motor recovery, 40 with few studies testing functional recovery across multiple domains. These studies have provided crucial information about glial differentiation, neuronal gene regulation, and other molecular changes induced by NIBS.…”
Section: Results Summary and Recommendationsmentioning
confidence: 99%
“…Evidence-based translational barriers: (a) Preclinical response domains . Most preclinical studies (approximately 60%) focused on the use of tDCS or rTMS to promote neuroprotection and plasticity after stroke in relation to motor recovery, 40 with few studies testing functional recovery across multiple domains. These studies have provided crucial information about glial differentiation, neuronal gene regulation, and other molecular changes induced by NIBS.…”
Section: Results Summary and Recommendationsmentioning
confidence: 99%
“…86 Another study by Buetefisch et al also suggested the neuroprotective effects of rTMS in stroke mice, as proven by the upregulated expression of anti-apoptotic proteins, reduction of pro-apoptotic molecules and decrease of cell death. 87 It has also been reported that magnetic stimulation is able to increase the plasticity of synapses and improve neurological dysfunction after injuries. Qian et al used rTMS as an efficient and painless brain stimulation approach to treat rats with traumatic brain injury (TBI).…”
Section: The Responses Of Neural Cells To Various External Physical S...mentioning
confidence: 99%
“…International Journal of Stroke, 19 (2) recovery, 40 with few studies testing functional recovery across multiple domains. These studies have provided crucial information about glial differentiation, neuronal gene regulation, and other molecular changes induced by NIBS.…”
Section: Knowledge Gap 5: Optimized and Individualized Nibs Protocolsmentioning
confidence: 99%